Wrestling with Job: defiant faith in the face of suffering - Kynes, William L. (IVP Academic, An imprint of InterVarsity Press, 2022)
"The unique richness of the book of Job cannot be simply explained-it must be experienced. In this collaboration between pastor father and scholar son Bill and Will Kynes, you will find exposition, spiritual application, and a deeper look at the thornier aspects of the text, equipping you to consider how you too might practice defiant faith"--